Bahasa Inggris: Bahasa Indonesia - Moh Rizwan Rizal; Sugihardjo Sugihardjo; Putri Permatasari (Hasanuddin University, 2023)
The development of rice which is quite well-known in Klaten Regency is the rojolele srinuk rice variety. The rojolele srinuk rice variety has become the identity of Klaten Regency because it has its own characteristics and features a fluffier, savory and fragrant taste compared to other rices. The existence of the rojolele srinuk rice variety can motivate rice farmers in Klaten Regency to cultivate it. The motivation of rice farmers in Klaten Regency can be formed because there are factors that influence it, such as being able to increase income and have the convenience of obtaining seeds of the Rojolele Srinuk variety of rice. Therefore, it is necessary to conduct research on the motivation of farmers in cultivating the rojolele srinuk rice variety in Klaten Regency. This study aims to 1) Assess the motivation level of farmers in cultivating the Rojolele Srinuk variety of rice in Klaten Regency. 2) Knowing the factors forming the motivation of farmers in cultivating Rojolele Srinuk variety rice in Klaten Regency. 3) Analyzing the relationship between the forming factors of motivation and the motivation level of farmers in cultivating the Rojolele Srinuk variety of rice in Klaten Regency.